Is Ankle Arthritis More Disabling than Midfoot Arthritis and 1st MTPJ Arthritis?. Issue 3 (11th September 2017) - Ramaskandhan, Jayasree Ramas; Siddique, Malik
Category: Ankle Arthritis, Midfoot/Forefoot Introduction/Purpose: There is wide array of outcome tools available for assessment of level of pain and symptoms in osteoarthritis, there are less disease and region specific outcome measures to evaluate the level of disability caused by arthritis in ankle, mid foot arthritis (including Talo-navicular joint, Calcaneo-cuboid joint and tarso metatarsal joints) and 1st Metatarso phalangeal joints. We aimed to measure the level of disability incorporating elements of physical, mental and social well-being using patient reported outcome measures as recommended by the International classification of Functioning, disability and health (ICF) Methods: This is a prospective data series, patients with arthritis of ankle, mid foot or 1st MTPJ who were diagnosed in new patient clinic were asked to take part in this survey. They completed a questionnaire consisting of MOX-FQ (Manchester Oxford Foot Questionnaire), EQ-5D (General Health Status) and FAOS (Foot and Ankle Outcome Scores). Patients were grouped in to 3 groups (Group A - ankle arthritis. Group B - midfoot arthritis (either Talo navicular, Calcaneo-cuboid or TMT joint); Group C - arthritis of 1st Metatarso-phalangeal joint of the foot). The results of summary scores were calculated for responses to individual questions and compared between the groups. Demographic factors were included in the statistical analysis carried out using SPSS Version 22, Illinois. Results are reported as follows Results: There were 26 patients in (Group A); 12 patients in (Group B) and 19 patients in (Group C). There was no difference in mean age of patients between groups (p>0.05) For components in MOX-FQ, there was no difference in pain scores (p=0.353) between the groups. For difficulty with walking/standing, Group A patients reported significantly worse scores (77 ± 19.4) when compared to Group C (53.7 ± 35.5). There was no difference in scores between groups for social function component of MOX- FQ (p=0.487). For EQ-5D, although Group C patients reported higher scores they failed to achieve statistical significance (p>0.05). For FAOS, Group A patients reported significantly lower scores for pain and symptoms, ADL, ability to take part in Sports/Recreation (p=0.008) and Quality of Life (p=0.003). Conclusion: In conclusion, although patients with ankle arthritis, mid foot arthritis and 1st MTP joint arthritis report similar level of disability in terms of general health and social function, patients with ankle arthritis reported higher level of disability in terms of pain, difficulty with standing/ Walking, ability to do Activities of Daily living, ability to take part in recreational activities and overall Quality of Life.